Association of mannose-binding lectin 2 gene polymorphisms with Guillain-Barré syndrome - Jahan, Israt; Hayat, Shoma; Khalid, Mir M.; Ahammad, Rijwan U.; Asad, Asaduzzaman; Islam, Badrul; Mohammad, Quazi D.; Jacobs, Bart C.; Islam, Zhahirul (Scientific reports, 2022)
Complement activation plays a critical role in the pathogenesis of Guillain-Barré syndrome (GBS), a debilitating immune-mediated neuropathy. Mannose-binding lectin (MBL) is a complement activation factor of lectin pathway which as genetic host factor may influence the susceptibility or severity of GBS. We investigated the frequency of MBL2 promoter (− 550H/L and − 221X/Y) and functional region (exon 1 A/O) polymorphisms and their association with disease susceptibility, clinical features and serum MBL among GBS patients ( n = 300) and healthy controls ( n = 300) in Bangladesh. The median patient age was 30 years (IQR: 18–42; males, 68%). MBL2 polymorphisms were not significantly associated with GBS susceptibility compared to healthy controls. HL heterozygosity in GBS patients was significantly associated with mild functional disability at enrolment ( P = 0.0145, OR, 95% CI 2.1, 1.17–3.82). The HY, YA, HA and HYA heterozygous haplotypes were more common among mildly affected ( P = 0.0067, P = 0.0086, P = 0.0075, P = 0.0032, respectively) than severely affected patients with GBS. Reduced serum MBL was significantly associated with the LL, OO and no HYA variants and GBS disease severity. No significant association was observed between MBL2 polymorphisms and electrophysiological variants, recent Campylobacter jejuni infection or anti-ganglioside (GM1) antibody responses in GBS. In conclusion, MBL2 gene polymorphisms are related to reduced serum MBL and associated with the severity of GBS.